Circadian tuning with metameric white light: Visual and non-visual aspects. (October 2021) - Aderneuer, T; Stefani, O; Fernández, O; Cajochen, C; Ferrini, R
The growing awareness of the biological effects of electric light on humans has stimulated ample research. New research has been devoted to lighting solutions that dynamically change their colour to mimic spectral changes of daylight. However, in some situations, the visual properties of light must be preserved, such as when working under standardised lighting conditions to do colour correction in post-production. We have investigated the possibility to tune circadian effects using white lights that are spectrally different but nonetheless appear as a similar white tone. Our simulation results, for example, sets of light-emitting diodes, indicate that it is possible to modulate circadian light effects from 0.20 to 0.41 circadian stimulus by combining light-emitting diodes to create neutral white (4000 K) light. However, the results also show that the solutions combining single-colour light-emitting diodes leading to similar range between maximum and minimum circadian stimulus (ΔCS > 0.20) have a CRI below 80. Combining narrowband light-emitting diodes with a broadband white light-emitting diode improves the colour-rendering quality, and we show how far circadian light effects can be tuned according to common theoretical models. The aim is to maintain the natural cycle of melatonin levels as much as possible with high light stimulus in the morning and low light stimulus in the evening. Therefore, we show what maximum and minimum circadian effects are possible with a given set of light-emitting diodes.